ITE provision in minority language contexts: The case of Wales and Ireland. - Dunne, Claire Marie; Thomas, Enlli M. (John Benjamins Publishing, 2022)
Within the broader contexts of language maintenance, revitalization and use, schools have an important role to play in the early transmission of minority or minoritized languages. Through effective classroom-based practices, teachers can offer rich, continuous linguistic experiences for the young people they teach that can lead to long-term, sustained engagement with language over time. How effective a given approach or practice may be in delivering a linguistic outcome in different contexts depends to a large extent on the skills and competence of the teacher involved (Fitzpatrick et al., 2018, p. 59), and the skills and competence of the teacher are usually rooted in their early experiences as student teachers. Initial teacher education (ITE) programmes are therefore central to the delivery of effective classroom-based practices and fundamental in generating autonomous teachers who can explore critically the different pedagogical approaches as they pertain to minority language contexts. This paper provides a comparative overview of the current issues and challenges facing ITE for primary education in two distinct minority language settings, namely Wales and Ireland. Both settings provide Welsh-medium or Irish-medium immersion education, as well as English-medium education offering Welsh or Irish as statutory subjects up to age 16. Both contexts also offer ITE programmes through the medium of Welsh or Irish, catering specifically for those student teachers wishing to teach in immersion settings. Both contexts face a number of shared challenges in terms of the content, design and delivery of an effective ITE programme for the context. We therefore highlight areas in which resources and methodologies could be shared amongst all those involved in ITE where minority language maintenance is a key component of education.
Keywords: initial teacher education; Education; Immersion Education; Minority language; Bilingual education; Content and Language Integrated Learning; Welsh; Irish; Education--Ireland